Birocracy Politization Typology in Structural Official Replacement (Case Study in Regional Government of North Maluku Province) - Bustamil Muhidin; Suswanta Suswanta (CV. Ridwan Publisher, 2023)
The phenomenon of structural structural change in the regional government bureaucracy is still colored by the practice of politicization. This politicization is carried out with various types including functional types, formal types and administrative types. These various types are used to select and place people who are considered capable of securing and protecting the powers of regional heads. the study aims to find out Birocracy Politization Typology in Structural Official Replacement in terms of functional politicization types. This study uses a qualitative method with a case study approach. This study found out that the change of structural officials carried out after the election of regional heads and the deciding variable of bureaucratic politicization is the regulation that forms the legal basis for replacing structural officials with politicization indicators, which are practices, mechanisms and authority in the replacement of structural officials.